Efek Farmakologis Ekstrak Daun Cleome gynandra L. : Sebuah Tinjauan Sistematis - Kadek Ayu Intan Pitaloka; I Nyoman Gede Wardana; I Wayan Sumardika; Ida Ayu Alit Widhiartini (Journal of Pharmaceutical and Sciences, 2026)
Background: Cleome gynandra L. is a leafy medicinal plant widely used in traditional medicine across Asia and Africa. Although its rich phytochemical profile has attracted growing scientific interest, the existing evidence on its pharmacological effects remains fragmented and inconsistent across studies. Objective: This systematic review aims to synthesize and critically evaluate the pharmacological effects of C. gynandra leaf extract reported over the past decade. Methods: A systematic literature search was conducted in PubMed, ScienceDirect, and Medline for articles published between January 2016 and December 2025, following the PRISMA guidelines. Studies reporting the pharmacological activities of C. gynandra leaf extract using in vitro or in vivo approaches were included. Data extraction and quality assessment were performed independently by two reviewers. Results: A total of seven studies met the inclusion criteria. The findings consistently demonstrated that C. gynandra leaf extract possesses antioxidant, antibacterial, anticancer, hepatoprotective, and antimalarial activities, which are largely attributed to its diverse phytochemical constituents, including flavonoids, phenolic compounds, and triterpenoids. However, substantial heterogeneity was observed across studies in terms of extraction methods, experimental designs, dosage regimens, and outcome parameters. All available evidence remains at the preclinical stage, with no clinical trials identified. Conclusion: The current evidence suggests that C. gynandra leaf extract exhibits promising pharmacological potential. Nevertheless, the high degree of methodological variability and the absence of clinical studies preclude definitive conclusions regarding its therapeutic efficacy and safety. Future research should prioritize standardized methodologies, mechanistic investigations, and well-designed clinical trials to validate the medicinal value of this plant.